Analisis Etika Bisnis Islam dalam Transaksi Jual Beli Online di Indonesia - D Purnomo; Teguh Lesmana; Fitri Novilia; Djoko Wijono; Asri Ady Bakri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of the world of technology and increasingly advanced internet networks has an impact on people's consumption techniques, thus giving rise to new shopping channels, namely online. People's need for fast information is very easy, can be accessed by anyone, anytime and anywhere. Internet technology has a very big effect on trade or business. Can access information on goods from anywhere, both from prices, specifications, and making purchase transactions. The purpose of this study is to analyze Islamic business ethics in online buying and selling transactions in Indonesia. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that the application of Islamic business ethics in online buying and selling transactions in Indonesia has not been fully implemented, because there are still some sellers who violate the principles of Islamic business ethics. One example is that there are still some sellers who provide escorts or summaries so that the goods received by the buyer do not match the specifications, the seller does not respond to goods complained about by the buyer, and there are still sellers who do not accept returns.